Beauty Standard Construction and its Influence on Consumerism in Indonesia’s Next Top Model - Irene Gloria; Liem Satya Limanta (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
Indonesia's Next Top Model (INTM) is a television program that airs under a license from America's Next Top Model. Through this event, the participants are challenged to show their abilities and talents to become the best model. This event is also part of the symbolic recognition of who is the best and prettiest model. When the contestants' abilities are recognized, they will receive the title of Indonesia's Next Top Model. This thesis aims to analyze the beauty standards determined by the judges in the talent show, Indonesia's Next Top Model, as well as their influence on consumerism.